Controlling HIV-1: Non-Coding RNA Gene Therapy Approaches to a Functional Cure - Ahlenstiel, Chantelle L.; Suzuki, Kazuo; Marks, Katherine; Symonds, Geoff P.; Kelleher, Anthony D. (Frontiers in Immunology, 2015)
The current treatment strategy for HIV-1 involves prolonged and intensive combined antiretroviral therapy (cART), which successfully suppresses plasma viremia. It has transformed HIV-1 infection into a chronic disease. However, despite the success of cART, a latent form of HIV-1 infection persists as integrated provirus in resting memory CD4+ T cells. Virus can reactivate from this reservoir upon cessation of treatment and hence HIV requires lifelong therapy. The reservoir represents a major barrier to eradication. Understanding molecular mechanisms regulating HIV-1 transcription and latency are crucial to developing alternate treatment strategies which impact upon the reservoir and provide a path towards a “functional cure” in which there is no detectable viremia in the absence of cART. Numerous reports have suggested ncRNAs are involved in regulating viral transcription and latency. This review will discuss the latest developments in ncRNAs, specifically short interfering (si)RNA and short hairpin (sh)RNA, targeting molecular mechanisms of HIV-1 transcription, which may represent potential future therapeutics. It will also briefly address animal models available for testing potential therapeutics and current gene therapy clinical trials.